GALANT: a Cytoscape plugin for visualizing data as functional landscapes projected onto biological networks - Camilo, Esther [UNESP]; Bovolenta, Luiz A. [UNESP]; Acencio, Marcio L. [UNESP]; Rybarczyk-Filho, Jose L. [UNESP]; Castro, Mauro A. A.; Moreira, Jose C. F.; Lemke, Ney [UNESP] (Oxford University Press, 2013)
Network-level visualization of functional data is a key aspect of both analysis and understanding of biological systems. In a continuing effort to create clear and integrated visualizations that facilitate the gathering of novel biological insights despite the overwhelming complexity of data, we present here the GrAph LANdscape VisualizaTion (GALANT), a Cytoscape plugin that builds functional landscapes onto biological networks. By using GALANT, it is possible to project any type of numerical data onto a network to create a smoothed data map resembling the network layout. As a Cytoscape plugin, GALANT is further improved by the functionalities of Cytoscape, the popular bioinformatics package for biological network visualization and data integration.